FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG (Perusahaan Manufaktur yang terdaftar di BEI pada tahun 2011-2013) - Hesty Erviani Zulaecha; Erna Suyatiningsih (JMB : Jurnal Manajemen dan Bisnis, 2016)
The aim of this reseachis to obtain empirical evidence about the factors that affect the audit report lag. The factors that affect the audit report lag are profitability (ROA), solvency (DEBT RATIO), the size of the Public Accounting Firm (KAP) and the Age of the company (AGE). The Sampleof the research consists of 64 manufacturing companies that listed in Indonesia Stock Exchange (BEI) by sampling using purposive sampling. Analysis of data using multiple linear regression with significant by 5%. These results of the reseach is adjusted R2 has a value of 10.6,% with the remaining 89.4% is influenced by other factors. Test F shows that together ROA, DEBT, KAP and AGE have an influence on the audit report lag. While the t test showed that AGE has a positive significant effect, KAP has a significantly negative effect on the audit report lag. ROA and DEBT no effect.